(untitled) (Interdisciplinary Journal of Nursing and Health, 2026)
Introduction. The Early Care Pathway (ECP) model was recently introduced in some emergency departments (EDs) in Northern Italy to enhance patient care through earlier nursing intervention. Although its benefits are recognized, little is known about how nurses experience and adapt to this organizational innovation. This study explores emergency nurses’ lived experiences with the ECP model, focusing on its impact on practice, professional identity, and interprofessional collaboration. Methods. A qualitative study was conducted using Interpretative Phenomenological Analysis (IPA). Seventeen nurses (12 females, 5 males; age range 24–55) with direct experience of the ECP model participated in semi-structured interviews between July and August 2024. Participants were purposively selected based on criteria including ECP training and at least three months of experience using the model. Interviews were audio-recorded, transcribed verbatim, translated into English, and analyzed following the IPA framework. Rigor was ensured through bracketing, audit trails, member checking, and triangulation. Results. Five interrelated themes emerged: (1) Deepening the nurse-patient connection – The ECP model enhanced the quality of interaction, promoting empathy, trust, and patient satisfaction through focused, uninterrupted time; (2) Empowerment and professional identity growth – Nurses reported increased autonomy, recognition, and decision-making capacity. The model reinforced their clinical judgement and enabled a more meaningful expression of their role; (3) Streamlining care through organizational innovation – ECP improved care efficiency by transforming waiting time into active care, promoting faster interventions and optimized workflows; (4) Fostering communication and team synergy – The model enhanced interdisciplinary collaboration and improved nurse-doctor dialogue. Nurses experienced more fluid team communication and greater involvement in early care decisions; (5) Navigating challenges and overcoming barriers – Implementation obstacles included resistance from physicians, ambiguity in role delineation, and workload concerns. However, most nurses expressed that these challenges were outweighed by the model’s benefits. Conclusion. The ECP model has a transformative impact on emergency nursing, fostering deeper patient relationships, enhancing professional identity, streamlining care, and strengthening teamwork. While implementation challenges exist, nurses overwhelmingly view the model as a valuable innovation that enriches both patient care and their professional experience. Understanding these lived experiences is essential for guiding future implementations and addressing contextual barriers.